Organizational and economic mechanism for developing business processes in the sphere of household services, using the example of the fit service car service chain: an ecosystem approach - Artem D. Gruzdo (Наука Красноярья)
In the highly competitive market of consumer services, efficient development of business processes is the basis for improving the quality of service, reducing costs and creating sustainable demand. An ecosystem approach to process management allows not only to optimize current resources, but also to create conditions for partnership and integration with other market participants. The article considers the organizational and economic mechanism for developing business processes in the sphere of consumer services using car services as an example. The organizational and economic mechanism is aimed at both regulating relationships in the ecosystem based on the formation of a network of values and institutions, and at developing business processes of enterprises in the sphere of consumer services (car services), which contributes to improving the quality of service and customer satisfaction. The balance of values of stakeholders is considered as the basis for developing business processes of enterprises in the sphere of services. In accordance with the presented concept of the ecosystem model for the development of business processes of car service enterprises, the structure of the organizational and economic mechanism, including institutional, axiological, economic, organizational and communication (network) instruments, is considered.